Pengaruh Good Corporate Governance Dan Intensitas Modal Terhadap Konservatisme Akuntansi - Ferlika Putri Susanto; Suwarno Suwarno (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The utilization of traditionalism can unquestionably affect monetary revealing issues for an organization. Presently, traditionalism procures the upsides and downsides of its application in an organization. However, it is evident that every business must implement sound corporate governance. Bookkeeping traditionalism can be impacted by administrative possession, autonomous magistrates, review quality, and capital force. Therefore, the goal of this study is to demonstrate whether or not these variables can influence accounting conservatism. This study utilizes a quantitative methodology with the estimation of foreordained factors. The populace incorporates all assembling organizations with purposive testing technique. Using the boostrapping method and the T-test, the research findings were evaluated. The outcomes showed that administrative possession and free chiefs affect bookkeeping traditionalism. While the review council and capital force impact review traditionalism. It is clear from the findings that they are consistent with several previous studies and that not all actors have a significant impact on accounting conservatism. Keywords: Accounting conservatism, Managerial ownership, Independent commissioner, Audit quality, Capital intensity